2013
DOI: 10.1097/prs.0b013e31829588b3
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Adipose-Derived Stromal Vascular Fraction Cells after Co-implantation with Fat Grafts

Abstract: The authors show convincing evidence for dynamic changes of stromal vascular fraction cells after co-implantation with fat grafts. The results prove the principle that implanted stromal vascular fraction cells can survive in the ischemic microenvironment of fat grafts and participate in the process of adipogenesis and angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…In this study, the protein of Perilipin A coating lipid droplets in adipocytes was applied to assess the injury degree of adipocytes. Only the healthy adipocytes were Perilipin A-positive, and therefore we were able to easily discriminated living and dead adipocytes timely and accurately [29]. As a result, the number of dead adipocytes in the ALLG group was less than in the AFT group at 7 and 14 days.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, the protein of Perilipin A coating lipid droplets in adipocytes was applied to assess the injury degree of adipocytes. Only the healthy adipocytes were Perilipin A-positive, and therefore we were able to easily discriminated living and dead adipocytes timely and accurately [29]. As a result, the number of dead adipocytes in the ALLG group was less than in the AFT group at 7 and 14 days.…”
Section: Discussionmentioning
confidence: 88%
“…ASCs can promote vascularization by its paracrine functions and multipotential differentiation [27] .They have the property of secreting various proangiogenic cytokines, such as vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), insulin growth factor (IGF), and leptin [28]. Moreover, ASCs can also directly differentiate into endothelial cells to promote neovascularization besides the paracrine mechanism [29]. In this study, as shown by CD34 immunofluorescence, syngeneic ASCs increased the capillary density in agreement with previous studies [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…Stromal vascular fraction cells can survive in the local region of fat injection for a long time, differentiate into adipocytes, and participate in vascular regeneration. 24 However, the mechanism for the sharp decrease of cells we observed is still obscure. The implanted fat tissues suffer from ischemia and hypoxia during the early stages after implantation.…”
Section: Discussionmentioning
confidence: 86%
“…The result from this study showed that, compared to the fat grafts without SVF, fat tissues transplanted with SVF had higher survival rate since 14 days after injection (P=0.001). Moreover, stem or progenitor cells in SVFs are believed to be helpful in tissue regeneration by differentiation (34). At the end of 63 days of follow-up, SVF group had a significant advantage in volume of survived fat tissue (PG0.001).…”
Section: Discussionmentioning
confidence: 99%